Attitudes Towards Interprofessional Education Among Counselling Psychology Graduate Students in Canada - Klaver, Ellen; Kelly, Nicole; Greidanus, Elaine; Harris, Gregory E.; Whelton, William (Canadian Journal of Counselling and Psychotherapy, 2019)
Students (N = 77) from 3 counselling psychology graduate programs in Canada completed an online questionnaire to assess their attitudes towards interprofessional education (IPE). Data were gathered on students’ demographic characteristics, readiness for IPE, and perceptions about teamwork in healthcare. Most participants were female, aged 23–35 years, and were enrolled in a masters-level program with no previous interprofessional work experience. Participants’ readiness for IPE and professional stereotype scores were comparable to, if not greater than, scores reported by students in different healthcare disciplines in other studies. Thematic analysis revealed 4 key messages that counselling psychology students learned about interprofessional practice from their graduate programs: (a) there are limited IPE training opportunities for counselling psychology graduate students, (b) teamwork enhances patient care, (c) teamwork may threaten client confidentiality, and (d) the public and other healthcare professions undervalue psychologists in healthcare settings. Implications for the educational and professional development of counselling psychology in Canada are discussed.